Analysis of the Use of JKN Mobile Applications on the Effectiveness of Registration Queues at RSUD Bandung Kiwari - Agustin, Wulan Trie; Sari, Irda (International Journal of Applied and Scientific Research, 2024)
One of the technologies that is developing today is network technology and the internet. The rapid development of information technology has encouraged BPJS Kesehatan to carry out digital innovation by launching a digital application known as the "Mobile JKN" application. This application aims to overcome the problem of registration queues that are often complained about by participants. This study aims to determine the use of the JKN Mobile application on the effectiveness of the registration queue at Bandung Kiwari Hospital, The research method used is a qualitative method with a descriptive approach, with data collection techniques through interviews, observation, and documentation. The source of information in this study came from 1 head of Medical Records and JKN installation and 10 JKN Mobile application users and non-users. Effectiveness measurement through three indicators, namely: accuracy factor, time factor, and service provider style factor. The results showed that the effectiveness of services through the JKN Mobile application at Bandung Kiwari Hospital has not been fully effective because in its use there are still often obstacles or problems found in the application.